Central bank design in a non-optimal currency union: A lender of last resort for government debt? - Peter Spahn (Research On Money in the Economy (ROME), 2016)
Without a Lender of Last Resort for government debt, multiple equilibria in bond markets may ensue where default emerges for non-fundamental reasons. The stabilising power of central bank interventions does not build on a real debt depreciation via inflation, but on a swap of bonds and central bank reserves that bear lower interest rates. Budget constraints and balance sheet considerations do not necessarily pose severe restrictions for such a monetary backstop policy. However in EMU, the ECB is not authorised for supporting national fiscal policy. But a return to a no-bailout regime requires large debt cuts.
Keywords: E5; E6; 330; currency union; lender of last resort; central bank reserves; central bank budget constraint